(untitled) (Comprehensive Journal of Science, 2025)
quality of accounting disclosure in industrial companies operating in Misurata. The study population consisted of 50 industrial companies registered with the Misurata Chamber of Commerce and Industry, from which a random sample of 30 companies was selected. The research adopted a descriptive and analytical approach. A questionnaire was designed as the primary tool for data collection, covering the main dimensions of the study. Data were analyzed using the statistical software SPSS version 27. The findings revealed that corporate governance has a statistically significant positive effect on the quality of accounting disclosure. The study recommended that companies comply with governance requirements and promote a culture of governance among stakeholders more broadly through issuing guidelines, instructions, and participating in conferences that support corporate governance.